English language learners' use of self-regulatory strategies for foreign language anxiety in China. (August 2018) - Guo, Yan; Xu, Jinfen; Liu, Xudong
Abstract: This article reports on an exploratory study of Chinese EFL learners' use of self-regulatory strategies for foreign language anxiety (FLA). A 31-item questionnaire was developed based on focus group interviews and theoretical input drawn from areas of research including learning strategy, self-regulated learning, and cognitive therapy. A total of 753 non-English major undergraduate EFL learners from seven universities in central China participated in the study. Both an Exploratory Factor Analysis and a Confirmatory Factor Analysis were conducted to identify the specific categories of strategy while General Linear Model univariate procedures were performed to detect any difference in strategy use among the students of different FLA levels. Findings revealed that six categories of strategy were identified, with Cognitive Strategy, Metacognitive (Appraisal) Strategy, and Affective Strategy being favored by the students. FLA levels exerted a significant impact on the students' strategy use. The low-anxiety group demonstrated significantly higher frequency in the use of all the six categories of strategy except Avoidance Strategy and Affective Strategy. The high- and mild-anxiety groups, in contrast, respectively used Avoidance Strategy and Affective Strategy most frequently. Based on these findings, practical implications for alleviating learners' FLA in foreign language teaching are provided.